2005
DOI: 10.1345/aph.1e272
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Pain and Analgesic Treatment in the Home-Dwelling Elderly

Abstract: Although analgesics are commonly used by elderly patients, it appeared that many patients were still experiencing daily interfering pain and pain at rest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…In addition, a relatively high proportion of persons with persistent chronic pain did not use any analgesic drug, which is in agreement with previous studies. [20][21][22] As far as we are aware, this is the first populationbased longitudinal documentation of noncancer-related chronic musculoskeletal pain in a community-dwelling older population with such a long follow-up time. An important strength of our study was that the data were collected annually from the same population.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, a relatively high proportion of persons with persistent chronic pain did not use any analgesic drug, which is in agreement with previous studies. [20][21][22] As far as we are aware, this is the first populationbased longitudinal documentation of noncancer-related chronic musculoskeletal pain in a community-dwelling older population with such a long follow-up time. An important strength of our study was that the data were collected annually from the same population.…”
Section: Discussionmentioning
confidence: 90%
“…17,18 Although older individuals have the highest prevalence of prescription analgesic use, 19 previous studies have suggested that nonetheless pain is inadequately treated, that is, 15% to 20% of older people reporting daily pain do not take any analgesic drugs. [20][21][22] Considering the individual suffering and costs for society, it is important to allocate thorough research to the course of persistent pain and factors related to it. Furthermore, research focusing on the older age group should have high priority, because of the growth of the older population worldwide.…”
mentioning
confidence: 99%
“…A study in Finland reported that 70.0% of the elderly community aged over 75 years made use of one or more anti-inflammatory or analgesic. 23 Pokela et al 14 also studied a population of Finnish elderly persons and reported that 45.4% used antiinflammatory drugs and analgesics. Another study in Switzerland reported that 22.0% of elderly participants used anti-inflammatories and analgesics 24 while a study of Brazilian elderly persons in Curitiba, Paraná, found that 37.0% of the study population used these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain impairs activities of daily living and mobility, and may predict the progression of disability in home-dwelling older persons [3]. Chronic pain can be classified according to its pathophysiology into nociceptive pain, neuropathic pain, and pain without a known somatic background [4].…”
Section: Introductionmentioning
confidence: 99%